KEY TRENDS IN SUPPLY PEACE AND RESTORATION - M.S. Nuridinov (Bright Mind Publishing, 2025)
"Holy Motherland, it is an honor to protect it!" ideas about the important principles of the idea and the factors of civic duty were put forward
Keywords: To promote and inculcate the ideas of patriotism, responsibility, spirituality, enlightenment, peace and stability in the minds of young people.